Interactive e-module using Zoom Cloud Meeting platform to reduce misconceptions on salt hydrolysis material - Maria Erna; Lenny Anwar; Mazidah Mazidah (Journal of Education and Learning (EduLearn), 2021)
This study aimed to determine the effectiveness of using an interactive e-module to reduce students’ misconceptions on salt hydrolysis material at grade XI in senior high school. This study implemented a pre-experiment with one group pretest-posttest research design, which utilized one class as the experimental class. Samples were selected by using purposive sampling technique, and it was obtained one class as the experimental class, namely class XI in State Madrasah Aliyah 1 Pekanbaru, Riau, Indonesia. Before giving the treatment, the sample was administered a pretest and after the treatment, they were given a posttest. The pretest and posttest questions occupied three-tier multiple choice questions. The reduction of misconceptions on Salt Hydrolysis material after using the interactive e-module was 16.21%. The study found that interactive e-modules effective to reduce misconceptions on salt hydrolysis material was significant.